Do Consumers Consider the Healthfulness of Wine in Republic of Korea? - Jinkyung Choi; Jinlin Zhao; Jiin Yang (Beverages, 2023)
Purpose: Wine is an alcoholic beverage considered to have health benefits when consumed in moderation. Studies have investigated the healthfulness of wine via various approaches; however, given that wine consumption behavior is evolving, fresh data are needed. There is a paucity of evidence on the perceived mental health benefits of wine; hence, this study examined consumers’ perceptions of wine healthfulness separately for each physical and mental health benefit and compared them with wine consumption behaviors. Design/methodology/approach: A quantitative data collection method was used. The questionnaires were given to participants in South Korea who had consumed wine in the six months before the survey. A total of 304 responses were collected for further analysis. A paired t-test, ANOVA, and descriptive analysis were used to analyze the data. Findings: This study found that respondents perceived higher mental health benefits than physical health benefits from wine consumption. Demographic characteristics showed significant differences in the mental or physical health benefits of wine. Consumers who believed in the physical health benefits of wine preferred white wine over red wine; however, consumers who believed in the mental health benefits of wine had no preferences. Originality: This study suggests that segmented marketing tools are needed due to the various characteristics of wine consumers. In addition, to encourage a healthy drinking environment, marketing should focus on moderation for both the wine industry and consumers. Furthermore, consumers’ consideration of the mental health benefits of wine consumption cannot be underestimated compared to the physical health benefits of wine consumption; however, wine is also regarded as an alcoholic beverage that needs to be consumed with consideration of health concerns in various restrictions.